Prítomnost bakteriální infekce u pacientů s akutním krvácením v důsledku portální hypertenze--nase zkusenosti - Husová, L; Lata, J; Senkyrík, M; Juránková, J; Husa, P (Vnitrni lekarstvi, 2003)
Acute haemorrhage from the upper gastrointestinal tract is a frequent and serious complication which affects 20-60% patients with cirrhosis of the liver and portal hypertension. It is assumed that bacterial infections can be the direct cause of haemorrhage but accurate data on the influence of infection on the development and course of haemorrhage are lacking. Acute haemorrhage as a result of portal hypertension has a very high mortality, 30-50%, and an early relapse of haemorrhage occurs in as many as 40% of these patients. Most recent meta-analyses indicate that bacterial infection is an independent prognostic factor in failure of haemostasis and has a significant impact on the mortality of these patients. The authors examined for the presence of bacterial infection (blood, urine, throat, ascites) 25 patients with cirrhosis of the liver and acute haemorrhage as a result of portal hypertension and compared the results with a group of 25 patients with cirrhosis of the liver and portal hypertension without acute haemorrhage. According to the results in patients with acute haemorrhage due to portal hypertension there is a significantly higher incidence of bacterial infections than in patients with cirrhosis of the liver and portal hypertension without acute haemorrhage. The results confirm the necessity to administer antibiotic prophylaxis to cirrhotic patients with varicose bleeding, not only to patients with symptoms and evidence of infection but also in their absence. Antibiotic prophylaxis extends the survival period of these patients.
Keywords: Humans; lidé středního věku; jaterní cirhóza; bakteriální infekce; Female; Aged; dospělí; senioři; lidé; Liver Cirrhosis; Adult; ženské pohlaví; Male; gastrointestinální krvácení; Middle Aged; Gastrointestinal Hemorrhage; Aged, 80 and over; senioři nad 80 let; Bacterial Infections; portální hypertenze; mužské pohlaví; Acute Disease; akutní nemoc; Hypertension, Portal